Financiamento de longo prazo no Brasil: Um mercado em transformaç\~ao - Ernani Teixeira Torres Filho; Fernando Nogueira da Costa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper has two objectives. Initially, seeks to review the main theses contained in the Brazilian economic literature on the role of the Brazilian Development Bank (BNDES) and its historical role in financing Brazilian economic development. The second objective is to analyze the perspective of long-term financing in the country and the future role of BNDES in this scenario. Recent financial innovations in Brazil are already transferring long-term financing from the books of banks to the portfolios of private wealth managers. The key assumption is that long-term financing in Brazil in the coming years will go through a great transformation and become more similar, although keeping its own differences, to what is already being practiced in other more advanced capital markets. This will require a change in the behavior of the main financial players, notably BNDES. This perspective should change the course of the academic debate, still far too ideologically polarized.
Keywords: G17; G18; G21; G24; G38; 330; financing long term; financial innovation